What makes entrepreneurship research interesting? Reflections on strategies to overcome the rigour–relevance gap. Issue 1 (1st January 2016) - Frank, Hermann; Landström, Hans
Abstract: As entrepreneurship researchers compete to have their work published and universities strive to attract the best entrepreneurship scholars, it is appropriate to examine what makes entrepreneurship research interesting. Interesting studies are usually defined as well-crafted and well-written studies that challenge established knowledge, and produce new theories and findings. This paper examines entrepreneurship scholars' views on the characteristics of interesting entrepreneurship research by means of a qualitative approach. Eight focus group interviews comprising junior and senior entrepreneurship scholars were conducted. A core finding is that interesting studies must be relevant to practice. However, the institutionalization of entrepreneurship as an academic field has favoured rigour at the cost of relevance, leading to scholars' frustration with the rigour–relevance gap. In this paper, we analyse various dimensions of interestingness and reflect on strategies for overcoming the rigour–relevance gap, with particular focus on the creation of applicative knowledge.